A decade of progress in marine evolutionary biology. (25th December 2022) - De Wit, Pierre; Faust, Ellika; Green, Leon; Jahnke, Marlene; Pereyra, Ricardo T.; Rafajlović, Marina
Abstract: This article summarizes the Evolutionary Applications Special Issue, "A decade of progress in Marine Evolutionary Biology." The globally connected ocean, from its pelagic depths to its highly varied coastlines, inspired Charles Darwin to develop the theory of evolution during the voyage of the Beagle. As technology has developed, there has been a dramatic increase in our knowledge about life on our blue planet. This Special Issue, composed of 19 original papers and seven reviews, represents a small contribution to the larger picture of recent research in evolutionary biology, and how such advancements come about through the connection of researchers, their fields, and their knowledge. The first European network for marine evolutionary biology, the Linnaeus Centre for Marine Evolutionary Biology (CeMEB), was developed to study evolutionary processes in the marine environment under global change. Though hosted by the University of Gothenburg in Sweden, the network quickly grew to encompass researchers throughout Europe and beyond. Today, more than a decade after its foundation, CeMEB's focus on the evolutionary consequences of global change is more relevant than ever, and knowledge gained from marine evolution research is urgently needed in management and conservation. This Special Issue, organized and developed through the CeMEB network, contains contributions from all over the world and provides a snapshot of the current state of the field, thus forming an important basis for future research directions.